EFEKTIFITAS MEDIA PUZZEL GIZI TERHADAP KEBERHASILAN PEMBERIAN MP-ASI MENU SEIMBANG 4 BINTANG : The Effectiveness Of Nutritional Puzzel Media On The Success Of Provision Of Mp-Asi A Balanced 4 Star Menu - Wahida yuliana (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2022)
Media Puzzel Nutrition is an innovative teaching aid in providing health education about complementary foods for breast milk. The community must be provided with knowledge so that they change their behavior to want to provide proper nutrition. Efforts are being made to prevent stunting. We can prevent this stunting by supporting nutrition in the first 1000 days of life in the form of successful breastfeeding. The highest prevalence of stunting in East Java was in 2017. In the 10th rank there is Probolinggo Regency with a stunting prevalence of 49.43%. This figure is far above the national average of 37.2%. This condition requires an approach in the first 100 days of life by mobilizing the family whose role is to influence changes in the behavior of the baby's consumption patterns according to need. This study aims to determine the effectiveness of the use of nutrition puzzle media on the success of giving MP-ASI with a balanced 4-star menu. This study uses a quasi experimental research design. The population is 30 mothers who have babies aged 5-6 months. The sampling technique used is simple random sampling. The analysis used is a chi-square statistical test. The results of this study are nutrition puzzle media that are effective in giving complementary feeding with a balanced diet of 4 stars with p = 0.00.